The Most Common Cause of Fever in International Travelers Visiting Kasih Ibu Hospital Denpasar for the 2019-2020 Period - Suryanditha, Putu Arya; Wijaya, I Dewa Gede Harry; Budiapsari, Putu Indah; Widhidewi, Ni Wayan (Muhammadiyah Medical Journal, 2023)
Background: Fever is one of the most common symptoms that international travelers complain of due to various causes. Fever is associated with mild to severe illnesses, such as Coronavirus Disease 19, typhoid fever, dengue fever, malaria, chikungunya, or gastrointestinal infection. Purpose: This study aimed to determine the most common cause of fever in international travelers visiting Kasih Ibu Hospital Denpasar from 2019 to 2020. Methods: This cross-sectional study using medical records of international travelers with chief complaints of fever uses purposive sampling. Result: The age of the subject was dominated by the adult age group in 2019 (77.3%) and 2020 (77.1%), with more females in 2019 (50.8%) while more males in 2020 (57.8%), 2019 the most common cause of fever was dengue infection (50.8%) while in 2020 the most common cause of fever was COVID-19 (53.5%). Conclusion: Dengue was the most common cause of fever in 2019, and COVID-19 was the most common cause of fever in 2020.